Electron transport layer material and quantum dot light emitting diode

By doping two-dimensional layered semiconductor materials in inorganic nanoparticles, the problem of interfacial charge accumulation between the electron transport layer and the quantum dot light emitting layer in the quantum dot light emitting diode is solved, and the performance and lifetime of the device are improved.

CN119907399AActive Publication Date: 2025-04-29YUNGU GUAN TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311413558.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

Existing quantum dot light emitting diodes (QLEDs) have interface charge accumulation between the electron transport layer and the quantum dot light emitting layer, resulting in exciton quenching and device performance degradation.

Method used

Doping two-dimensional layered semiconductor materials in inorganic nanoparticles changes the Fermi energy level and work function of the electron transport layer, reducing the energy barrier between the electron transport layer and the quantum dot luminescent layer, and alleviating the accumulation of interface charge.

Benefits of technology

By doping two-dimensional layered semiconductor materials, the performance of QLED is improved, the external quantum efficiency and lifetime of the device are improved, making it more suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907399A_ABST
    Figure CN119907399A_ABST
Patent Text Reader

Abstract

The invention relates to an electron transport layer material and a quantum dot light emitting diode. The material of the electron transport layer comprises inorganic nanoparticles and a two-dimensional layered semiconductor material doped in the inorganic nanoparticles, and the mass fraction of the two-dimensional layered semiconductor material in the material of the electron transport layer is 0.001%-20%. When the electron transport layer material is used for manufacturing an electron transport layer, the two-dimensional layered semiconductor material with the content range is doped in the inorganic nanoparticles, so that the Fermi level of the electron transport layer can be changed, the work function of the electron transport layer can be adjusted, and the electron transport layer can be manufactured. Therefore, the energy barrier between the electron transport layer and the quantum dot light-emitting layer is reduced, the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer is relieved, the device performance is improved, and wide application is facilitated. In addition, the invention also relates to a quantum dot light-emitting diode, the quantum dot light-emitting diode comprises an electron transport layer, and the electron transport layer comprises any one of the electron transport layer materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of light-emitting devices, and in particular to an electron transport layer material and a quantum dot light-emitting diode. Background Art

[0002] Quantum dots are semiconductor nanostructures that bind excitons in three spatial directions. Due to the unique optical properties of quantum dots, such as the continuous tunability of the emission wavelength with size and composition, narrow emission spectrum, high fluorescence efficiency and good stability, quantum dot-based light-emitting diodes (QLEDs) have received extensive attention and research in the display field. At the same time, QLED displays also have many advantages that LCDs cannot achieve, such as large viewing angle, high contrast, fast response speed, and flexibility, so they are expected to become the next generation of display technology.

[0003] Commonly used quantum dot light-emitting diodes (QLEDs) are generally organic-inorganic hybrid structures, and the electron transport layer (ETL) generally uses inorganic nanoparticles with high electron mobility, such as ZnO, so that the electron mobility is much greater than the hole mobility, that is, the electron injection and transmission capabilities are much greater than the hole injection and transmission. However, excessive electron injection leads to a large amount of charge accumulation at the QD / ETL interface, and exciton quenching leads to a decrease in device performance. Summary of the invention

[0004] Based on this, it is necessary to provide an electron transport layer material and a quantum dot light emitting diode to address the problem of how to improve device performance.

[0005] An electron transport layer material comprises inorganic nanoparticles and two-dimensional layered semiconductor materials doped in the inorganic nanoparticles, wherein the mass fraction of the two-dimensional layered semiconductor materials in the electron transport layer material is 0.001% to 20%.

[0006] When the electron transport layer material of the technical solution of the present invention is used to make the electron transport layer, since the two-dimensional layered semiconductor material in the above-mentioned content range is doped into the inorganic nanoparticles, it is possible to change the Fermi level of the electron transport layer and adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, alleviating the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer, improving the device performance, and facilitating wide application.

[0007] In a feasible implementation, the two-dimensional layered semiconductor material is selected from at least one of aniline-coated Si nanoparticles, transition metal sulfides and transition metal selenides.

[0008] In a feasible implementation, the transition metal sulfide is selected from at least one of molybdenum disulfide and tungsten disulfide.

[0009] In a feasible implementation, the transition metal selenide is selected from at least one of tungsten diselenide and indium selenide.

[0010] In a feasible implementation, the mass fraction of the two-dimensional layered semiconductor material to the electron transport layer material is 0.01% to 5%.

[0011] In a feasible implementation, the mass fraction of the two-dimensional layered semiconductor material to the electron transport layer material is 0.01% to 0.5%.

[0012] In a possible implementation, the inorganic nanoparticles include metal oxides.

[0013] In a feasible implementation, the metal oxide is selected from at least one of ZnO and ZnMgO.

[0014] A quantum dot light emitting diode comprises a quantum dot light emitting layer and an electron transport layer located on one side of the quantum dot light emitting layer, wherein the electron transport layer comprises any of the above-mentioned electron transport layer materials.

[0015] The above-mentioned quantum dot light-emitting diode has a simple structure. Because its electron transport layer contains the electron transport layer material described in the present invention, it can change the Fermi level of the electron transport layer and adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, alleviating the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer, and improving the device performance.

[0016] In a feasible implementation, the thickness of the electron transport layer is 5 nm to 100 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 FIG. 4 is a schematic diagram of a quantum dot light emitting diode according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0020] The electron transport layer material of one embodiment includes inorganic nanoparticles and two-dimensional layered semiconductor materials doped in the inorganic nanoparticles, and the mass fraction of the two-dimensional layered semiconductor materials in the electron transport layer material is 0.001% to 20%.

[0021] Among them, inorganic nanoparticles refer to a class of materials that can be used as the main material of the electron transport layer. Among them, the main function of the two-dimensional layered semiconductor material is to change the Fermi level of the electron transport layer and adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, alleviating the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer, and improving the device performance.

[0022] On the basis of the above-mentioned embodiment, the two-dimensional layered semiconductor material is selected from at least one of aniline-coated Si nanoparticles (LCP), transition metal sulfides and transition metal selenides. Aniline-coated Si nanoparticles, transition metal sulfides and transition metal selenides are all two-dimensional layered semiconductor materials, and the valence band top energy level of such materials can reach between 6eV and 6.5eV (i.e., greater than or equal to 6 electron volts and less than or equal to 6.5 electron volts), and have excellent electrical conductivity and stability, and can thus change the Fermi level of the electron transport layer, adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, and relieving the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer.

[0023] Based on the above-mentioned embodiment, the transition metal sulfide is selected from at least one of molybdenum disulfide (MoS2) and tungsten disulfide (WS2).

[0024] Based on the aforementioned embodiment, the transition metal selenide is selected from at least one of tungsten diselenide (WSe2) and indium selenide (In2Se3).

[0025] On the basis of the above-mentioned implementation mode, the mass fraction of the two-dimensional layered semiconductor material in the electron transport layer material is 0.01% to 5%. When the mass fraction of the two-dimensional layered semiconductor material in the electron transport layer material is 0.01% to 5%, electron injection and transmission can be reduced, but the electrons are still slightly more than the holes, which does not affect the charge balance of the QLED device.

[0026] Based on the above implementation, the mass fraction of the two-dimensional layered semiconductor material to the electron transport layer material is 0.01% to 0.5%. At this time, the quantum dot light-emitting device using the electron transport layer material of this implementation has the best external quantum efficiency and lifespan.

[0027] In the aforementioned embodiment, the inorganic nanoparticles include metal oxides, and the metal oxides can be used as a host material of the electron transport layer.

[0028] On the basis of the above-mentioned embodiment, the metal oxide is selected from at least one of ZnO and ZnMgO. In other words, the metal oxide can be ZnO, ZnMgO or a mixture of the two.

[0029] When the electron transport layer material of the technical solution of the present invention is used to make the electron transport layer, since the two-dimensional layered semiconductor material in the above-mentioned content range is doped into the inorganic nanoparticles, it is possible to change the Fermi level of the electron transport layer and adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, alleviating the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer, improving the device performance, and facilitating wide application.

[0030] A quantum dot light-emitting diode according to one embodiment includes a quantum dot light-emitting layer and an electron transport layer located on one side of the quantum dot light-emitting layer, wherein the electron transport layer includes any of the above-mentioned electron transport layer materials.

[0031] Based on the above-mentioned embodiment, the thickness of the electron transport layer is 5 nm to 100 nm.

[0032] Furthermore, the quantum dot light-emitting diode also includes an anode, a hole injection layer, a hole transport layer and a cathode. The quantum dot light-emitting layer is arranged between the anode and the cathode, the hole transport layer is arranged between the anode and the quantum dot light-emitting layer, the hole injection layer is arranged between the anode and the hole transport layer, and the electron transport layer is arranged between the quantum dot light-emitting layer and the cathode.

[0033] It should be noted that the quantum dot light emitting diode of the present invention may be an upright structure or an inverted structure.

[0034] When the quantum dot light emitting diode can be in an upright structure, see Figure 1 A quantum dot light-emitting diode 100 of one embodiment includes an anode 110, a hole injection layer (HIL) 120, a hole transport layer (HTL) 130, a quantum dot light-emitting layer (QD) 140, an electron transport layer (ETL) 150 and a cathode 160 which are stacked in sequence.

[0035] The anode 110 is located below the hole transport layer 130 , and the material of the anode 110 may be, for example, ITO or IZO.

[0036] The material of the hole injection layer 120 may be a conductive polymer, such as PEDOT:PSS, or a high work function n-type semiconductor, such as HAT-CN, MoO3, WO3, V2O5, Rb2O, etc. It is understandable that the hole injection layer 120 may not be provided.

[0037] The material of the hole transport layer 130 is a semiconductor material, for example, at least one selected from TFB, PVK, Poly-TPD, NPB, CBP, TCTA and NiO.

[0038] The quantum dot light emitting layer 140 is located above the hole transport layer 130. The material of the quantum dot light emitting layer 140 is selected from at least one of II-VI compounds, III-V compounds, I-III-VI compounds, IV simple substances and perovskite quantum dots.

[0039] Among them, II-VI compound semiconductors include but are not limited to ZnCdSeS, CdSe / ZnSe, CdSeS / CdS, CdSe / CdS / ZnS, ZnCdS / ZnS and ZnCdSeS / ZnS. III-V compound semiconductors include but are not limited to InP and InP / ZnS. I-III-VI compound semiconductors include but are not limited to CuInS, AgInS, CuInS / ZnS and AnInS / ZnS. IV single-element semiconductors include but are not limited to Si, C and Graphene.

[0040] The electron transport layer 150 contains the electron transport layer material described in any embodiment of the present invention, and the electron transport layer material includes inorganic nanoparticles and two-dimensional layered semiconductor materials doped in the inorganic nanoparticles, and the mass fraction of the two-dimensional layered semiconductor materials in the electron transport layer material is 0.001% to 20%.

[0041] The cathode 160 is located above the electron transport layer 150 , and the material of the cathode 160 may be, for example, Al or Ag.

[0042] Of course, the quantum dot light-emitting diode of the present invention is not limited to the above-mentioned embodiments, and may also be an inverted structure.

[0043] When preparing the above-mentioned quantum dot light-emitting diode, the above-mentioned two-dimensional layered semiconductor material can be first mixed into the ETL material, and a stable liquid can be obtained after stirring and mixing evenly, and then the device preparation can be started, and HIL spin coating, HTL spin coating, QD spin coating, ETL spin coating and electrode evaporation can be performed in sequence to obtain the above-mentioned quantum dot light-emitting diode.

[0044] The above-mentioned quantum dot light-emitting diode has a simple structure. Because its electron transport layer contains the electron transport layer material described in the present invention, it can change the Fermi level of the electron transport layer and adjust the work function of the electron transport layer, thereby reducing the energy barrier between the electron transport layer and the quantum dot light-emitting layer, alleviating the interface charge accumulation between the electron transport layer and the quantum dot light-emitting layer, and improving the device performance.

[0045] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following embodiments.

[0046] Example 1

[0047] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0048] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0049] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0050] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0051] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 0.01% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0052] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 Pa to obtain a cathode aluminum electrode with a thickness of 100 nm.

[0053] Example 2

[0054] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0055] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0056] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0057] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0058] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 0.05% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0059] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 Pa to obtain a cathode aluminum electrode with a thickness of 100 nm.

[0060] Example 3

[0061] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0062] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0063] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0064] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0065] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 0.1% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0066] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 A cathode aluminum electrode was obtained by evaporating a 100 nm thick layer under Pa.

[0067] Example 4

[0068] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0069] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0070] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0071] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0072] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 0.5% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0073] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 A cathode aluminum electrode was obtained by evaporating a 100 nm thick layer under Pa.

[0074] Example 5

[0075] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0076] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0077] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0078] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0079] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 1% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0080] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 Pa to obtain a cathode aluminum electrode with a thickness of 100 nm.

[0081] Example 6

[0082] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0083] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0084] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0085] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0086] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 5% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0087] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 Pa to obtain a cathode aluminum electrode with a thickness of 100 nm.

[0088] Example 7

[0089] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0090] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0091] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0092] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0093] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 10% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0094] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 Pa to obtain a cathode aluminum electrode with a thickness of 100 nm.

[0095] Example 8

[0096] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0097] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0098] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0099] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0100] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of 20% WS2-ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0101] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 A cathode aluminum electrode was obtained by evaporating a 100 nm thick layer under Pa.

[0102] Comparative Example 1

[0103] Step 1: Cleaning of ITO anode conductive glass: Use deionized water, acetone, and isopropanol for 10 minutes of ultrasonic treatment, blow dry with nitrogen, place in a culture dish, and treat with ozone for 20 minutes before use;

[0104] Step 2: Preparation of hole injection layer: 100 μL of the prepared HIL was dissolved in ethyl benzoate solution and spin-coated on the anode at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230° C. for 30 minutes to obtain a hole injection layer;

[0105] Step 3: Preparation of hole transport layer: 100 μL of the prepared HTL was dissolved in chlorobenzene solution and spin-coated on the hole injection layer at 3000 rpm for 30 seconds, and then annealed on a flat heating table at 230°C for 30 minutes to obtain a hole transport layer;

[0106] Step 4: Preparation of quantum dot light-emitting layer: Take 50 μl of the prepared HTL and dissolve it in n-octane solution and spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain the quantum dot light-emitting layer;

[0107] Step 5: Preparation of electron transport layer of doped layered materials: Take 100 μL of ZnO ethanol solution, spin-coat it on the hole transport layer at 3000 rpm for 30 seconds, and then anneal it on a flat heating table at 100°C for 5 minutes to obtain a quantum dot light-emitting layer;

[0108] Step 6: Cathode preparation: Evaporation of aluminum Al electrode at 4×10 -4 A cathode aluminum electrode was obtained by evaporating a 100 nm thick layer under Pa.

[0109] Performance Test:

[0110] The EQE (external quantum efficiency) and lifetime of the QLEDs of Examples 1 to 8 and Comparative Example 1 were tested. The testing method is as follows. The test data is shown in Table 1.

[0111] EQE test method: using PR-655 spectrometer.

[0112] Life test method: Use a constant current source to input current to the QLED and record the curve of its brightness changing over time; commonly used life parameters include T 95 , which indicates the time it takes for the brightness of the QLED to decay from the initial value to 95% of the initial value.

[0113] Table 1 Performance test results of QLED of Examples 1 to 8 and Comparative Example 1

[0114]

[0115] It can be seen from Table 1 that compared with the QLED of Comparative Example 1, the external quantum efficiency and lifetime of the QLEDs of Examples 1 to 8 of the present invention are better, indicating that doping two-dimensional layered semiconductor materials into the inorganic nanoparticles of the traditional electron transport layer can improve device performance.

[0116] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0117] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An electron transport layer material, characterized in that: The electron transport layer material comprises inorganic nanoparticles and two-dimensional layered semiconductor materials doped in the inorganic nanoparticles, and the mass fraction of the two-dimensional layered semiconductor materials in the electron transport layer material is 0.001% to 20%.

2. The electron transport layer material according to claim 1, characterized in that The two-dimensional layered semiconductor material is selected from at least one of aniline-coated Si nanoparticles, transition metal sulfides and transition metal selenides.

3. The electron transport layer material according to claim 2, characterized in that: The transition metal sulfide is selected from at least one of molybdenum disulfide and tungsten disulfide.

4. The electron transport layer material according to claim 2, characterized in that The transition metal selenide is selected from at least one of tungsten diselenide and indium selenide.

5. The electron transport layer material according to claim 1, characterized in that The mass fraction of the two-dimensional layered semiconductor material to the electron transport layer material is 0.01% to 5%.

6. The electron transport layer material according to claim 1 or 5, characterized in that: The mass fraction of the two-dimensional layered semiconductor material to the electron transport layer material is 0.01% to 0.5%.

7. The electron transport layer material according to claim 1, characterized in that The inorganic nanoparticles include metal oxides.

8. The electron transport layer material according to claim 7, characterized in that: The metal oxide is selected from at least one of ZnO and ZnMgO.

9. A quantum dot light emitting diode, characterized in that: It comprises a quantum dot light-emitting layer and an electron transport layer located on one side of the quantum dot light-emitting layer, wherein the electron transport layer comprises the electron transport layer material according to any one of claims 1 to 8.

10. The quantum dot light emitting diode according to claim 9, characterized in that: The thickness of the electron transport layer is 5nm to 100nm.

Citation Information

Patent Citations

  • High-efficiency quantum dot light emitting diode with self-assembly polymer hole transmission layer structure

    CN105609651A

  • Electroluminescent device, preparation method thereof and display device

    CN112349853A

  • Quantum dot light emitting diode, two-dimensional material and preparation method thereof

    CN115377315A

  • Two-dimensional material semiconductor device

    TWM624914U

  • Electroluminescent device, production method thereof, and display device including the same

    US20230209995A1